If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1u + -3 = 12 Reorder the terms: -3 + -1u = 12 Solving -3 + -1u = 12 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1u = 12 + 3 Combine like terms: -3 + 3 = 0 0 + -1u = 12 + 3 -1u = 12 + 3 Combine like terms: 12 + 3 = 15 -1u = 15 Divide each side by '-1'. u = -15 Simplifying u = -15
| 0.4t=0.5+0.6t | | -51+8=n | | 4/5-678*7 | | 3x^2+24x-7=0 | | 0.2(8-6h)=h | | 14x^2-11xy-15y^2=0 | | 3x+47=180 | | 12.25-.75=x | | 4+(a/5)=2 | | 1+6=3+2x | | -3(3y-4)-y=-2(y-4) | | 1-9/6x=2/5 | | 1+3y=5/3y | | (3x-1)/4=-5/11 | | 2/3(6y+9)=20 | | 4(x-1)-2(3x+5)=3x-1 | | a+2b=50 | | 5x=3/7 | | 5x^3=3x^2 | | 12+3p=2p+4 | | 2x=3y-10 | | A=5k/7y | | 12x-8=-20 | | 3x+5=9y-4+z | | a+a+7=3+a | | 3[4(3x+1)-(10x-9)]=7x+9 | | x=2y^2-4 | | (2x-3)/4=(3-2x)/6 | | 2x-(1/x)=1 | | x^2-x-x=0 | | 2X+7X-12=33 | | X^2-2x-12=-12 |